Faculty perceptions of student plagiarism and interventions to tackle it: a multiphase mixed-methods study in Qatar - Mai A. Mahmoud; Ziyad R. Mahfoud; Ming-Jung Ho; John Shatzer (BMC Medical Education, 2020)
Abstract Background The widespread use of the internet and other digital resources has contributed to the escalation of plagiarism among medical students and students of other healthcare professions. Concerns were raised by faculty at Weill Cornell Medicine-Qatar (WCM-Q), a branch of Weill Cornell Medicine of Cornell University in New York, who had been observing plagiarism in students’ assignments. Methods To identify the extent of plagiarism practices and their contributing factors, a two-phase mixed-method research study was conducted, comprising a survey administered in 2013, followed by longitudinal interventions, and a second survey in 2017 to measure the impact of the interventions. Results By Phase II, overall observed plagiarism incidents per year decreased from 44 to 28%, and the number of faculty who observed no plagiarism incidents increased significantly from 12 to 37%. The faculty concerned about student plagiarism decreased by 33% [53.1 to 20%] between Phase I and Phase II. Conclusion When students are provided with information regarding what constitutes plagiarism and their institution’s policy in response to plagiarism incidents, they are less likely to engage in such practices.